Ensino Médio Técnico Profissional: um processo instrumental para a empregabilidade - Almeida, Angelita de Oliveira (2020)
The present study is inserted in the line of Work research, Society and Education of the Graduate Program in Education of Uberlândia Federal University, state of Minas Gerais, Brazil, and its general objective is to analyze and problematize Technical High School Education from the end of the XX century, considering the conception of a state social instrument with a view to the ideology of employability. The specific objectives are: To demonstrate how Professional Education was constituted as an instrument of social control by the State and Capital; analyze work as an educational principle that has its essence based on capitalist accumulation; unveil the contributions that Technical High School Education has to the social and professional life of young people; explain what is considered important to enter and / or remain in the labor market. In order to meet the proposed objectives, both from a theoretical and methodological point of view, we opted for the principles of Socio-Historical Theory, which is based on the assumptions of dialectical historical materialism, as it allows us to approach the researched object within an articulated social totality, preserving its specificities, connections and mediations when dialectically articulating the external aspects with the internal aspects of the reality in which the object is inserted. We start from the thesis that the technical professional training of medium level aims to train young people according to the ideological discourses of employability, aiming to guarantee their responsibility for their entry and / or maintenance in the labor market. When analyzing this proposal for education for work it was possible to understand how Technical High School Education is constituted as a set of functionalities and instruments vital to the expanded reproduction of capital, while ensuring the reproduction of neoliberal ideologies in educational relations and work.